PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, EARNING MANAGEMENT DAN KINERJA PERUSAHAAN - Nofryanti Nofryanti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
The company's activities which were initially only measured by prioritizing profits have now begun to shift to calculating social and environmental problems in their financial statements. The company is asked to be responsible for the environment and social through a non-financial report that is the report of Corporate social responsibility (CSR). The purpose of this study was to analyze the effect of CSR disclosure on company performance and management earnings on company performance. This research is quantitative with secondary data and uses eviews to test the influence between variables. The research sample is 34 companies listed on the Indonesia Stock Exchange that present financial reports and sustainability reports. The results showed that CSR disclosure had no effect on company performance and earnings management had a positive effect on company performance. It can be concluded that CSR disclosed by the company has not been able to improve company performance. CSR disclosure disclosed by the company will not always benefit the company, the high cost of CSR will have an impact on increasing company spending. Companies tend to use earning management patterns to improve their performance Keywords: CSR disclosure; Earning Management; Company Performance